Electronic learning among students at public universities in Ghana - Afful, D.; Boateng, J.K. (Cogent Education, 2023)
This study was planned to establish the extent of the usage and benefits of mobile technologies to learn by distance learners at the University of Ghana and the University of Education, Winneba. The study adopted an explanatory sequential mixed-method design. Structured questionnaires were administered to 400 dis tance learners selected by multi-stage sampling technique and phone interviews involving 20 participants selected by random sampling technique to collect data. Using the Relative Important Index and Thematic analysis, the findings show that respondents not only agreed to all the mobile learning academic activities and benefits raised in this study as relevant but fundamental to their studies. The five most important mobile learning activities by students are communicating with colleagues for information, participating in online courses, doing coursework assignments, holding meetings among colleagues and instructors, and forming networks with peers on a social media platform. The highest of the first five highest ranked benefits is finding relevant material for coursework with ease, studying at own pace in different environments, learning anywhere and anytime, receiving real-time information, and having quick access to coursework content. The findings of this study can encourage institutions offering distance education to build strategic electronic learning implementation plans and design guidelines by taking into consideration the highest-ranked important benefits and uses of mobile learning identified in this study.
Research Article
Keywords: Electronic learning; mobile learning; distance education